2016
DOI: 10.1016/j.brainres.2016.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Language effects in second-language learners: A longitudinal electrophysiological study of spanish classroom learning

Abstract: How do the neural mechanisms involved in word recognition evolve over the course of word learning in adult learners of a new second language? The current study sought to closely track language effects, which are differences in electrophysiological indices of word processing between one’s native and second languages, in beginning university learners over the course of a single semester of learning. Monolingual L1 English-speakers enrolled in introductory Spanish were first trained on a list of 228 Spanish words… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
1
16
0
2
Order By: Relevance
“…One goal of research focused on second language (L2) acquisition and processing in adults has been to shed light on how new words are learned as well as how new language systems are built and stored. Several investigators have used the temporal precision of event-related potentials (ERPs) to measure the adult brain's response to L2 words in proficient bilinguals and learners who have not yet attained L2 proficiency (e.g., Alvarez, Holcomb & Grainger, 2003; Hoshino, Midgley, Holcomb & Grainger, 2010; McLaughlin, Osterhout & Kim, 2004; Midgley, Holcomb & Grainger, 2009a; Pu, Holcomb & Midgley, 2016; Soskey, Holcomb & Midgley, 2016; Yum, Midgley, Holcomb & Grainger, 2014). In most studies, the authors have reported the N400 to be the most sensitive ERP component to manipulations of target language and L2 proficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One goal of research focused on second language (L2) acquisition and processing in adults has been to shed light on how new words are learned as well as how new language systems are built and stored. Several investigators have used the temporal precision of event-related potentials (ERPs) to measure the adult brain's response to L2 words in proficient bilinguals and learners who have not yet attained L2 proficiency (e.g., Alvarez, Holcomb & Grainger, 2003; Hoshino, Midgley, Holcomb & Grainger, 2010; McLaughlin, Osterhout & Kim, 2004; Midgley, Holcomb & Grainger, 2009a; Pu, Holcomb & Midgley, 2016; Soskey, Holcomb & Midgley, 2016; Yum, Midgley, Holcomb & Grainger, 2014). In most studies, the authors have reported the N400 to be the most sensitive ERP component to manipulations of target language and L2 proficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, several studies have shown that the N400 is sensitive enough to measure changes in the brain within the first few hours of L2 instruction (McLaughlin et al, 2004; Soskey et al, 2016; Yum et al, 2014). For example, McLaughlin et al (2004) found that the N400 response in native English speakers learning French could be used to discriminate L2 words from L2 pseudowords within the first 14 hours of instruction.…”
Section: Introductionmentioning
confidence: 99%
“…attention switching) from which both older and younger learners can benefit (Bak, Long, Vega-Mendoza, & Sorace, 2016); such cognitive benefits have also been found in delayed post-tests after six months of intensive FL learning via computer-based language training software and computer games (Wong et al, 2019) – although the opposite has also been reported (see e.g. Berggren et al, 2018; Ramos et al, 2017);there are advantages in additional (instructed) language learning for late bilinguals compared to monolinguals regardless of type of instruction (Cox & Sanz, 2015; Cox, 2017);effects measured during sentence comprehension using electroencephalography (EEG) become more similar between native speakers and adult L2 learners as a function of proficiency (Dowens, Vergara, Barber, & Carreiras, 2010; Soskey, Holcomb, & Midgley, 2016); furthermore, for older learners who make more L2 gains, switching between the L1 and the L2 is less effortful than for those with lower L2 proficiency after training (Van Der Meij, Cuetos, Carreiras, & Barber, 2011; Prat, Yamasaki, Kluender, & Stocco, 2016; Kliesch et al, 2018);although some implicit forms of learning – particularly those involving the acquisition of subtle probabilistic sequential regularities – show age-related declines, older adults are capable of statistical learning of the distributional information underlying grammatical form class categories, following brief auditory exposure to a subset of possible strings of the language (Schwab et al, 2016);despite equivalent performance, distinct neural networks characterise the ceiling of young and elderly French-speaking participants trained by means of a computerised Spanish word program (Marcotte & Ansaldo, 2014);the degree of difference in learning success between older individuals is predicted by various factors that may modulate benefit, such as prior knowledge of more than one language, which results in more successful L2 development (Pfenninger & Polz, 2018), language typology, bi- versus multilingualism, and age of acquisition (Antoniou & Wright, 2017);learner investment is likely to interact with the cognitive capacities of older learners, such that high cognitive demand leads to exhaustion, which may increase perceptions of low learning abilities and tiredness and reduce motivation (Ware et al, 2017);L2 learning plays a key role inasmuch as it addresses socio-affective issues – i.e. by preventing isolation, fostering linguistic flexibility, self-esteem and autonomy (Antoniou et al, 2013; Pot et al, 2018a).…”
Section: How Older Adults May Benefit From L2 Learningmentioning
confidence: 99%
“…effects measured during sentence comprehension using electroencephalography (EEG) become more similar between native speakers and adult L2 learners as a function of proficiency (Dowens, Vergara, Barber, & Carreiras, 2010; Soskey, Holcomb, & Midgley, 2016); furthermore, for older learners who make more L2 gains, switching between the L1 and the L2 is less effortful than for those with lower L2 proficiency after training (Van Der Meij, Cuetos, Carreiras, & Barber, 2011; Prat, Yamasaki, Kluender, & Stocco, 2016; Kliesch et al, 2018);…”
Section: How Older Adults May Benefit From L2 Learningmentioning
confidence: 99%
“…Previous studies demonstrated that ERPs may be sensitive to variables related to L2 instruction, such as proficiency (Elgort et al, 2015), individual differences (Tanner et al, 2013), immersion (Bowden et al, 2013) and the mid-and long-term effects of L2 classroom instruction (Soskey et al, 2016). Yet, while it is widely accepted in L2 instruction that an explicit focus on grammatical and lexical items yields the best learning effects (Spada & Tomita, 2010;Webb & Nation, 2017), remarkably few ERP studies sought to shed light on knowledge that has been acquired through either explicit or implicit instruction (i.e., the presence or absence of an attentional focus on L2 features).…”
Section: Erp Research and L2 Instructionmentioning
confidence: 99%